#### Answer

$M=\dfrac{P-C}{C}$

#### Work Step by Step

Subtract by $C$ to both sides:
$P-C=C+MC-C
\\P-C=MC$
Divide by $C$ on both sides:
$\dfrac{P-C}{C}=\dfrac{MC}{C}
\\\dfrac{P-C}{C}=M
\\M=\dfrac{P-C}{C}$

Published by
Pearson

ISBN 10:
0-13417-894-7

ISBN 13:
978-0-13417-894-3

$M=\dfrac{P-C}{C}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.